A compromised developmental trajectory of the infant gut microbiome and metabolome in atopic eczema. Issue 1 (9th November 2020) - Ta, Le Duc Huy; Chan, James Chun Yip; Yap, Gaik Chin; Purbojati, Rikky W.; Drautz-Moses, Daniela I.; Koh, Yanqing Michelle; Tay, Carina Jing Xuan; Huang, Chiung-Hui; Kioh, Dorinda Yan Qin; Woon, Jia Yun; Tham, Elizabeth Huiwen; Loo, Evelyn Xiu Ling; et al.
ABSTRACT: Evidence is accumulating that the establishment of the gut microbiome in early life influences the development of atopic eczema. In this longitudinal study, we used integrated multi-omics analyses to infer functional mechanisms by which the microbiome modulates atopic eczema risk. We measured the functionality of the gut microbiome and metabolome of 63 infants between ages 3 weeks and 12 months with well-defined eczema cases and controls in a sub-cohort from the Growing Up in Singapore Toward healthy Outcomes (GUSTO) mother-offspring cohort. At 3 weeks, the microbiome and metabolome of allergen-sensitized atopic eczema infants were characterized by an enrichment of Escherichia coli and Klebsiella pneumoniae, associated with increased stool D-glucose concentration and increased gene expression of associated virulence factors. A delayed colonization by beneficial Bacteroides fragilis and subsequent delayed accumulation of butyrate and propionate producers after 3 months was also observed. Here, we describe an aberrant developmental trajectory of the gut microbiome and stool metabolome in allergen sensitized atopic eczema infants. The infographic describes an impaired developmental trajectory of the gut microbiome and metabolome in allergen-sensitized atopic eczema (AE) infants and infer its contribution in modulating allergy risk in the Singaporean mother-offspring GUSTO cohort. The key microbial signature of AE is characterized by (1) an enrichment of Escherichia coli and Klebsiella pneumoniae which are associated with accumulation of pre-glycolysis intermediates (D-glucose) via the trehalose metabolic pathway, increased gene expression of associated virulence factors (invasin, adhesin, flagellin and lipopolysaccharides) by utilizing ATP from oxidative phosphorylation and delayed production of butyrate and propionate, (2) depletion of Bacteroides fragilis which resulted in lower expression of immunostimulatory bacterial cell envelope structure and folate (vitamin B9) biosynthesis pathway, and (3) accompanied depletion of bacterial groups with the ability to derive butyrate and propionate through direct or indirect pathways which collectively resulted in reduced glycolysis, butyrate and propionate biosynthesis. Graphical abstract: